Answer to ECG Quiz no. 19 - Okreglicki, A (SA Heart Journal, 2017)
In any bradycardia, especially in the peri-infarct setting, always suspect that the atrial rate could be faster. Look for nonconducted P- waves and consider AV block. Evidence of extensive conduction system disease in the postinfarct setting is an indication for backup/prophylactic ventricular pacing.